The role of kaolin particles in the performance of a carbamate-based biocide for water bacterial control - Pereira, Maria Olívia (2002)
The influence of kaolin particles on the activity of Pseudomonas fuorescens and on the efficacy of a carbamate-based biocide was investigated. The results indicated that kaolin particles stimulated the activity of the bacteria for all buffered pH values studied (5, 7, and 9); this effect being more evident for the tests carried out at pH 5 and 9. The presence of the clay in P. fuorescens suspensions decreased the efficiency of disinfection of the carbamate. The results also showed that kaolin was very effective in removing carbamate from the culture media. Therefore, the biocide concentration in the solution decreased, and consequently its availability to the bacteria was reduced. The results could be explained by the interaction between kaolin particles and carbamate and by the changes in the configuration of kaolin aggregates, depending on the pH value.